Evaluation de varietes de stylosanthes adoptees aux conditions de la zone subhumide du Nigeria - Mohamed-Saleem, M.A.; Otsyina, R.M. (1984)
It has always been difficult to find forage legumes with the production characteristics that can help maximise animal performance, and that are also adapted to the alternating wet and dry seasons of the subhumid zone of africa. Among the characters in demand are drought tolerance, good herbage production and plant persistence, either through regeneration after burning or heavy grazing or through self-seeding. Ideally they should also provide a good quality, standing hay crop that will help sustain aniamls through the dry season. Another important attribute is disease resistance, because the wet season usually provides conditions ideal for disease development and advancement. Stylosanthes spp. have many of the qualities demanded by African conditions but disease, in particular anthrracnose, caused by the fungus Colletotrichum gloeosporoides, has restricted their use. One species, S. hamata cv Verano, a selection made by scientists from Australia's Commonwealth Scientific and Industrial Research Organisation, combines disease resistance with the other favourable agronomic characteristics. This species has been widely planted in the tropics and has the potential for even further spread. However, whether Verano's disease resistance will be maintained is uncertain; if new virulent strains of anthracnose arise, they could nullify all the advantages of Verano-based pasture improvement. Because if this threat, ILCA scientists have screened a range of potentially useful Stylosanthes spp. that could either outperform, or substitute for Verano if its disease resistance breaks down. This paper gives details of their agronomic performance and disease resistance, and identifies four accessions that show promise for the subhumid zone.